Chestnut (Castanea sativa Mill.) industrial wastes as a valued bioresource for the production of active ingredients. (January 2018) - Squillaci, Giuseppe; Apone, Fabio; Sena, Luigi Michele; Carola, Antonietta; Tito, Annalisa; Bimonte, Marida; Lucia, Adriana De; Colucci, Gabriella; Cara, Francesco La; Morana, Alessandra
Graphical abstract: Highlights: Wastes from chestnut peeling process were used for production of active ingredients. The extract from inner and outer shells (IOCS) gave the highest phenolic yield. Gallic acid was the main phenolic compound identified in the extract. The IOCS extract showed remarkable properties for use in cosmetic formulations. Abstract: In the present study, by-products from chestnut peeling processing were used for the production of active ingredients. A blend of inner and outer chestnut shells (IOCS), and inner chestnut shells (ICS) were extracted through an eco-friendly method. IOCS extract contained the highest amount of phenolic molecules (205.99 ± 13.10 mg of Gallic Acid Equivalents/g of dry extract), and gallic acid was the most abundant compound among those identified by HPLC (63.51 ± 1.32 mg/g of dry extract). Condensed tannins represented the main phenolic fraction, accounting for 78.88% and 59.14% of the total phenolic compounds in IOCS and ICS extracts, respectively. Both extracts decreased the production of oxidized lipids in HaCaT keratinocytes after H2 O2 exposure. They showed protecting activity against inflammation as well, because the production of NO and iNOS, selected as inflammatory markers, was attenuated. IOCS extract (0.002%) showed greater activity with a reduction of 58% of NO and 43% of iNOS levels. The extracts also exhibited hydration capacity and protection against collagen degradation in HaCaT keratinocytes. All the results suggest that chestnut shell extracts can be potential active ingredients for cosmetic formulations devoted to the skin protection.